Photographs and labels: Against a criminology of innocence - K. Biber (Law Text Culture, 2006)
In 2000 the American photographer Taryn Simon began photographing people whose criminal convictions had been overturned through the work of the Innocence Project. Founded at Cardozo Law School, the Innocence Project aims to acquit falsely-convicted people by introducing evidence that was unavailable or not admitted during their trial. Mostly, the new evidence is derived from DNA technology which, for reasons of overwhelming scientific acceptance, is regarded as definitive. In 2003 Simon’s series The Innocents was exhibited at PS.1, an established centre of contemporary art in New York, with proceeds from sales going to support the continued work of the Innocence Project. That series has since been published in a book together with testimony from the photographed subjects derived from Simon’s interviews with them (Simon 2003).